Analysis of Regional Budget Management Performance at Regional Finance Agency of Pamekasan Regency - R. Agoes Kamaroellah; Moh. Syafik (The Winners, 2022)
The research aimed to analyze the performance of regional income, expenditure budget, and budget performance of revenue and expenditure at the Regional Finance Board of Pamekasan Regency during 2013-2016. In this descriptive quantitative research, data source was the Regional Expenditure's financial performance by considering the Budget Realization Report's information (Laporan Realisasi Anggaran/LRA). The analysis involved a three-step analysis, variance analysis, growth of regional expenditure, and suitability analysis of regional expenditure. The research reveals that most of the periods studied experience more expected differences, amplified with the target budget realization revenue from 2013-2016 has an average rate of 100,05%. The degree of decentralization of Kabupaten Pamekasan shows an average of 24,16%, which is considered below the percentage criteria of Original Local Government Revenue (OLGR) to Total Revenue Area (Total Pendapatan Daerah/TPD) ranging from 0,00-10,00%. Revenue Financial Performance District Pamekasan experiences an increase in Financial Performance Revenue, which is indicated by a positive growth rate of 8,29%. The level of dependency of Pamekasan Regency in 2013-2016 is very high, indicated by the average Local Financial Dependency Ratio above 50%. The results suggest that there is a dependence of the Pamekasan Government on central government or provincial government. The surplus occurs due to the intensification and extensification of original local growth revenue in the form of taxes, levies, and other income.